Toxic Leadership and Workplace Deviant Behavior among Gen Z Employees: The Mediating Role of Moral Justification and the Moderating Role of Resilience - Sari, Santi Retno; Sugiono, Edi; Nurwulandari, Andini (International Review of Management and Marketing, 2026)
This study examines how toxic leadership influences workplace deviant behavior among Gen Z employees in Indonesia by testing the mediating role of moral justification and the moderating role of resilience. Data were collected from 409 Gen Z employees in Jakarta through an email survey conducted in June and July 2025. The hypotheses were tested using partial least squares structural equation modeling (PLS-SEM). The findings show that toxic leadership significantly increases moral justification and workplace deviant behavior. Moral justification also significantly increases workplace deviant behavior and partially mediates the relationship between toxic leadership and deviance. Resilience weakens the positive relationship between toxic leadership and moral justification, and the moderated mediation effect is significant. The study contributes to the literature by identifying moral justification as a cognitive mechanism linking toxic leadership to deviant behavior and by positioning resilience as a boundary condition that reduces employees’ susceptibility to moral rationalization under toxic leadership.